On Relations between Dance and Movement: reflections about different meanings of movement and dance - Pedro Penuela (Universidade de São Paulo – USP, São Paulo/SP, Brazil) (Revista Brasileira de Estudos da Presença, 2018)
This work resumes some ideas proposed by the dance critic and scholar André Lepecki (2008), in order to reflect about the limits of a refusal of movement as a rupture with modernity and with a certain notion of choreography. For this purpose, a critical reading of the way dance history is conceived in this work is made, and then three nuances for the notion of movement are proposed, in order to point out that the conjunction between dance and movement is neither univocal nor have always the same political or conceptual implications.